Analisis Perancangan Sistem Kerja untuk Meningkatkan Keselamatan Kerja pada Pekerja di UKM Puput Pastel - Cahyani, Renita; Titong, Fitri Sylvianti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Small and Medium Enterprises (SMEs) have grown rapidly in Indonesia. Occupational safety in these SMEs still often occurs so that the level of work accidents experienced by workers is being splashed with cooking oil on the worker’s body while frying, falling due to slippery floors caused by cooking oil dripping on the floor, and the most common experience of workers is often complaining of pain in body parts, because they sit too long while working. Therefore, a work system design was carried out to improve work safety using a participatory ergonomics approach consisting of owners and employees. The purpose of this study is to avoid occupational health and safety risks, to improve worker welfare, and to reduce discomfort and human error. The results of the study showed that Puput Pastel SMEs need improvements in the frying process, namely a height of 90 cm, a width of the frying container and filter container of 70 cm, and chairs for employees with a width of 28 cm and a height of 65 cm.